The police in the community strategies for the 21st century - Miller, Linda S. (West/Wadsworth, 1997)
Intended for courses in Community Policing, Problem-Oriented Policing, or Policing in the Community, found in departments of criminal justice at two- and four-year schools.By focusing on the dual themes of community/police collaboration and problem-oriented policing, this text focuses on police involvement and interaction with the communities they serve. It explores the practical strategies of community policing as well as the philosophy behind the community policing movement.